Analyzing The Cost of Paddy Rice Labor in Indonesia: A Case Study in Ten Tons Syngenta Project - Nikmatul Khoiriyah; Mellysa Isnaini; Atiek Iriany; David Forgenie (University of Jember, 2023)
Rice is a commodity strategy and a basic food for nearly all Indonesian households. The purpose of this study is to describe the labor utilization and costs associated with all farming activities, as well as the income and efficiency of lowland rice farming. The study took place in the Ten Tons Syngenta area, specifically in Glanggang Village, Beji District, Pasuruan Regency, East Java. The study took place between August and September 2022. The sample was determined using a 20% random sampling technique, which in the collection of 22 samples of farmers. The research data were derived from primary sources and were gathered through direct interviews with farmers. The results indicated that labor costs is so high in land preparation and planting (53.50 percent) dominated work in lowland rice farming, followed by harvesting (17.37 percent), weeding (14.74 percent), fertilizing (8.92 percent), and spraying (5.4 percent ). Lowland rice farmers earn Rp. 5,381,567 per hectare and have an R/C ratio of 1.35. The application of advanced technology, particularly in land preparation and planting, is critical for increasing the income and efficiency of lowland rice farming in the Syngenta ten-ton area in order to support rice self-sufficiency in the run-up to Indonesia's 100th anniversary of independence in 2045.